PENGARUH METODE PRAKTIKUM TERHADAP KERJASAMA DAN PEMAHAMAN KONSEP SISWA PADA PEMBELAJARAN IPAS DI KELAS X TJKT SMKN 1 KAMAL - Sulastri; Hartati, Sulis Janu; Isman, Soubar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is generally to determine the influence of the practicum method on students' collaboration and understanding of concepts in science learning in Class X TJKT SMKN 1 Kamal. This research is quantitative research using Quasi Experimental Design. The population in this study was class X-1 with 24 students and class X-2 with 22 students. In proving and analyzing this, data collection is carried out using instruments in the form of observation sheets and questions. Meanwhile, the data analysis tests used are validity, reliability, homogeneity test, normality test, and simple linear regression test. The research results are based on hypothesis testing using the help of the IBM SPSS v.21 application, namely the first hypothesis obtained a sig value. 0.000 < 0.05 using a simple linear regression test, there is a significant influence on the use of practicum methods on cooperation in material on changes in the state of substances in class X TJKT SMKN 1 Kamal. The second hypothesis uses a simple linear regression test that the significance value is 0.000 < 0.05, there is an influence of the practical method on understanding the material on changes in the state of substances in class X TJKT SMKN 1 Kamal.